Concomitant latent pulmonary vascular disease leads to impaired global cardiac performance in heart failure with preserved ejection fraction. (2nd March 2023) - Schuster, Andreas; Schulz, Alexander; Lange, Torben; Evertz, Ruben; Hartmann, Finn; Kowallick, Johannes T.; Hellenkamp, Kristian; Uecker, Martin; Seidler, Tim; Hasenfuß, Gerd; Backhaus, Sören J.
ABSTRACT: Aims: The REDUCE‐LAP II trial demonstrated adverse outcomes after interatrial shunt device (IASD) placement in heart failure with preserved ejection fraction (HFpEF) attributed to latent pulmonary vascular disease (PVD). We hypothesized that exercise stress cardiovascular magnetic resonance (CMR) imaging could provide non‐invasive characterization of cardiac and pulmonary physiology for improved patient selection. Methods and results: The HFpEF‐Stress trial prospectively enrolled 75 patients with exertional dyspnoea and diastolic dysfunction. Patients underwent rest and exercise stress right heart catheterization, echocardiography and CMR imaging. Pulmonary artery and capillary wedge pressures, cardiac index (CI) and pulmonary vascular resistance (PVR) were calculated. Latent PVD was defined as increased PVR ≥ 1.74 Wood units during exercise stress. CMR assessed long‐axis strains (LAS) and filling volumes of all cardiac chambers. Right ventricular (RV) function was further quantified by stroke and peak flow volumes. Patients with latent PVD ( n  = 24) showed lower RV function (rest tricuspid annular plane systolic excursion, p  = 0.010; stress RV LAS, p  < 0.001) compared to patients without ( n  = 43). During exercise stress, RV stroke and peak flow volumes ( p  < 0.001) were reduced and led to impaired left atrial filling ( p  = 0.040) with a strong statistical trend to impaired ventricular (LV) filling ( p  = 0.098). This subsequently resulted in reduced LV‐CI ( p  < 0.001) despite preserved LV systolic function (LV LAS p  ≥ 0.255). The degree of RV dysfunction during exercise stress best predicted latent PVD (RV peak flow, area under the curve at rest 0.73 vs. stress 0.89, p  = 0.004). Conclusions: Latent PVD is a feature of HFpEF and is associated with impaired RV functional reserve, global diastolic filling and LV‐CI. This can be quantified by CMR and used to identify patients likely to benefit from IASD implantation. Abstract : Dependence of right ventricular (RV) functional reserve in patients with latent pulmonary vascular disease (PVD). Left: The figure shows the correlation of right ventricular peak flow (RV pFlow) and pulmonary vascular resistance (PVR) during exercise stress in patients with and without latent PVD as defined by PVR ≥1.74 Wood units (WU) during exercise. The black line shows the cut‐off for latent PVD. The red line shows the correlation of RV pFlow and PVR ( r  = −0.69, p  < 0.001). Right: In patients with latent PVD, the combination of impaired RV functional reserve and increased PVR during exercise stress leads to reduced left atrial and ventricular (LA/LV) filling with subsequently reduced cardiac output. Cardiac functional parameters are shown for exercise stress. CI, cardiac index; HFpEF, heart failure with preserved ejection fraction: NCD, non‐cardiac dyspnoea.